#TITLE_ALTERNATIVE# - ARDIANSAH PUTRA PANJAITAN (NIM : 12211039), GUSTI
As time goes by, the increase of energy demand will be a problem if we still rely on conventional energy resources. Non-conventional energy resources is the solution to this problem. Coalbed methane (CBM) is one of the non-conventional gas resources considered due to its large methane storage capability. Methane gas is generated and trapped inside the micro-fractures (cleats) and micro-pores (matrix) during the coalification process.The methane gas of are found mostly in the rock matrix due to the adsorption mechanism of the coal. The cleats also stores methane gas although at little amount since the cleats are mainly filled with water and used for the production mechanism. In a CBM reservoir, primary recovery is methane gas desorption from the coal matrix continued by gas transportation to the well using the cleats, face cleats, as main pathway. However, the recovery of methane gas by this method is quite low, only about 50% of the initial gas in place (Jichun Zue et al., 2003). This has caused the need for an alternative technique similar to Enhanced Oil Recovery for conventional wells but used to enhance methane gas production in a CBM reservoir. This technique is commonly called Enhanced Coal Bed Methane Recovery The common technique of ECBM recovery is CO2 or N2 gas injection. N2 injection will give a faster recovery than CO2. On the other hand, CO2 may not increase recovery as much as N2, however the breakthrough time will not be as fast as N2 and at the same time reduce greenhouse gas emission. With this principle, this paper introduces the concept of injecting solvent CO2-N2 as an ECBM recovery technique.Solvent CO2-N2 is defined as the amount of gas component fraction CO2 and N2 which are used as injectant thus the purpose of using this solvent is to gain optimum recovery factor with a relatively long breakthrough time and at the same time reducing greenhouse gas emissions. This paper focuses on determining recovery factor of CBM reservoir by injecting solvent CO2-N2 and analyzing the fraction of solvent components which gives the most optimum recovery factor. Moreover, this study also aimed to determine the effect towards the dewatering time due to this ECBM recovery technique. This study used synthetic data based on the Alberta field to model and simulate the reservoir. The best method with fraction of CO2 gas and N2 gas that produces the most optimum recovery factor will be discussed at the end of this paper.